THE EFFECT OF VALUE ADDED TAX AND ELECTRONIC SYSTEMS ON NETFLIX PURCHASE DECISIONS - Lili Syafitri; Vhika Meiriasari; Aprina Choiria (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine the effect of value added tax and electronic systems on Netflix purchasing decisions. The subjects of this study were active students of Universitas Indo Global Mandiri in 2024-2025. The sample of this study was obtained through the Slovin formula, resulting in 97 respondents. The data analysis technique was multiple linear regression, with validity and reliability tests used in measuring the questionnaire. Based on the results of the simultaneous test that has been conducted, it was found that the variables of Value Added Tax (X1) and Electronic Systems (X2) have a significant influence on Netflix Purchasing Decisions with a significance value of 0.000 <0.05. The results of the partial test show that the significance value of Value Added Tax (X1) on Netflix Purchasing Decisions is 0.032 <0.05. This means that H0 is rejected and H1 is accepted, which means that Value Added Tax has a positive effect on Netflix Purchasing Decisions. The significance value of Electronic Systems (X2) on Netflix Purchasing Decisions is 0.000 <0.05. This means that H0 is rejected and H2 is accepted, which means that the Electronic System has a positive influence on Netflix Purchase Decisions.